Impact and Treatment of Sarcopenia in Patients Undergoing Radiotherapy: A Multidisciplinary, AMSTAR-2 Compliant Review of Systematic Reviews and Metanalyses - Medici, Federica; Bazzocchi, Alberto; Buwenge, Milly; Zamagni, Alice; Macchia, Gabriella; Deodato, Francesco; Cilla, Savino; De Iaco, Pierandrea; Perrone, Anna Myriam; Strigari, Lidia; Rizzo, Stefania; Morganti, Alessio G. (Frontiers in Oncology, 2022)
Background. Sarcopenia (SP) is defined as the quantitative and functional impairment of skeletal muscles. SP is commonly related to older age and is frequent in cancer patients. In order to provide an overview of SP in patients treated with radiotherapy (RT) and to evaluate the current evidence, we analyzed the available systematic reviews and meta-analyses. Methods. Reviews were identified using PubMed, Scopus, and Cochrane library databases, without date restriction. Only systematic reviews and meta-analyses on the prognostic impact of SP and on any treatments aimed at reducing SP effect, in patients undergoing RT, were included in this review. The analyses not separately reporting the results in patients treated with RT were excluded. The quality assessment was performed using the Measurement Tool to Assess Systematic Reviews (AMSTAR-2). Results. From the 84 papers identified, 5 reviews met the inclusion criteria with 4 reports mainly including non-randomized trials. Three reviews on the effect of SP showed a significantly negative impact on overall survival in patients undergoing RT and/or chemoradiation for H&N cancers (HR: 1.63-2.07). Two reviews on interventional studies showed the possibility of: 1) improving physical functions through nutritional and physical interventions and 2) avoiding muscle wasting by means of sufficient protein intake. The quality assessment of the included review showed that 2 and 3 analyses are classifiable as having low and moderate overall confidence rating, respectively. Conclusions. The analyzed reviews uniformly confirmed the negative impact of SP in patients with H&N tumors undergoing RT and the possibility of improving muscle mass and function through nutritional and physical interventions. These results justify further research on this topic based on a more uniform SP definition and on a complete evaluation of the potentially confounding parameters.